Reduction of ATPase activity in the rice kinesin protein Stemless Dwarf 1 inhibits cell division and organ development. (1st September 2018) - Fang, Jingjing; Yuan, Shoujiang; Li, Chenchen; Jiang, Dan; Zhao, Linlin; Peng, Lixiang; Zhao, Jinfeng; Zhang, Wenhui; Li, Xueyong
Summary: Several kinesins, the ATP‐driven microtubule (MT)‐based motor proteins, have been reported to be involved in many basic processes of plant development; however, little is known about the biological relevance of their ATPase activity. Here, we characterized the Oryza sativa (rice) stemless dwarf 1 ( std1 ) mutant, showing a severely dwarfed phenotype, with no differentiation of the node and internode structure, abnormal cell shapes, a shortened leaf division zone and a reduced cell division rate. Further analysis revealed that a substantial subset of cells was arrested in the S and G2/M phases, and multinucleate cells were present in the std1 mutant. Map‐based cloning revealed that STD1 encodes a phragmoplast‐associated kinesin‐related protein, a homolog of the Arabidopsis thaliana PAKRP2, and is mainly expressed in the actively dividing tissues. The STD1 protein is localized specifically to the phragmoplast midzone during telophase and cytokinesis. In the std1 mutant, the substitution of Val‐40‐Glu in the motor domain of STD1 significantly reduced its MT‐dependent ATPase activity. Accordingly, the lateral expansion of phragmoplast, a key step in cell plate formation, was arrested during cytokinesis. Therefore, these results indicate that the MT‐dependent ATPase activity is indispensible for STD1 in regulating normal cell division and organ development. Abstract : Kinesins are ATP‐driven microtubule‐based motor proteins, but the biological relevance of their ATPase activity has rarely been explored. Here, we show that a reduction of ATPase activity in the rice phragmoplast‐associated kinesin‐related protein STD1 inhibited phragmoplast expansion and cell‐cycle progression, and caused a severely dwarfed phenotype, revealing its essential role in plant development.